Trails of Tears: raising awareness of displacement - Whalen, K (Refugee Studies Centre, University of Oxford, 2013)
Trails of Tears have arisen to draw attention and give legitimacy to multiple movements for fairness and justice, hoping to create a community of support strong enough to rectify a past injustice or prevent a future one